2018
DOI: 10.1177/0022022118783255
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Remote Acculturation Gaps Among Divorced Coparents and Children’s Adjustment in Turkey

Abstract: The possibility of differential remote acculturation to a distant culture is yet another chasm that divorced coparents must bridge as they raise their children in globalizing urban settings. This study explored the association between parental remote acculturation and perceived parental remote acculturation gaps in two acculturation domains (behavior, identity), in relation to children’s adjustment in Turkish divorced families. Altogether, 177 urban divorced mothers in Turkey reported their own and their ex-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Rather, there are various theoretical possibilities for individuals negotiating multiple cultures in RA, three of which have been found in empirical RA research studies. "Remote integration" refers to adopting one or more remote cultures while retaining the local ones(s) (e.g., Ferguson & Bornstein, 2012;, "remote separation" involves retaining the local culture(s) without adopting the remote one(s) (e.g., Ferguson & Bornstein, 2015;Giray & Ferguson, 2018), "remote assimilation" refers to adopting one or more remote culture(s) without retaining the local ones(s) (e.g., K. T. Galán Jiménez et al, 2019), and "remote marginalization" entails pulling away from local and remote cultures (and has not been found in any RA studies). These and other empirical studies have found remote separation (e.g., Jamaica) and remote integration (e.g., South Africa) to be the most common and remote marginalization to be the least common by virtue of the fact that it has not been observed.…”
Section: What Is Remote Acculturation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, there are various theoretical possibilities for individuals negotiating multiple cultures in RA, three of which have been found in empirical RA research studies. "Remote integration" refers to adopting one or more remote cultures while retaining the local ones(s) (e.g., Ferguson & Bornstein, 2012;, "remote separation" involves retaining the local culture(s) without adopting the remote one(s) (e.g., Ferguson & Bornstein, 2015;Giray & Ferguson, 2018), "remote assimilation" refers to adopting one or more remote culture(s) without retaining the local ones(s) (e.g., K. T. Galán Jiménez et al, 2019), and "remote marginalization" entails pulling away from local and remote cultures (and has not been found in any RA studies). These and other empirical studies have found remote separation (e.g., Jamaica) and remote integration (e.g., South Africa) to be the most common and remote marginalization to be the least common by virtue of the fact that it has not been observed.…”
Section: What Is Remote Acculturation?mentioning
confidence: 99%
“…A parent's cultural orientation is also associated with child outcomes. Giray and Ferguson (2018) asked divorced mothers in Turkey to self-report on their cultural orientation to the U.S. and Turkey. Mothers also reported on their perception of their ex-partner's Turkish or U.S. orientation and about their child's internalizing and externalizing behaviors.…”
Section: Family Dynamicsmentioning
confidence: 99%
“…Two quantitative studies in urban Jamaica estimate that at least one in three adolescents has a remotely bicultural “Americanized Jamaican” acculturation profile compared to their culturally traditional Jamaican peers due to their significantly stronger European American affinity, entertainment preferences, and even self-identification alongside their strong Jamaican identity (Ferguson & Bornstein, 2012, 2015). There is a compelling set of quantitative studies documenting remote biculturalism in various other samples across Africa, Asia, and Europe, albeit using different terminology and methods (Chen et al, 2008; Ferguson et al, 2017; Giray & Ferguson, 2018; McKenzie, 2018).…”
Section: Proximal and Remote Acculturationmentioning
confidence: 99%
“…My body is in Jamaica but my mind is in America” (Ferguson, ). RA has also been documented among youth far beyond the Caribbean – across Africa, Asia, Europe, Latin America, and Oceania (see Ferguson, Tran, Mendez, & van de Vijver, ; Giray & Ferguson, ). Adolescence and emerging adulthood are likely to be sensitive periods for RA given the prominence of identity construction (Jensen, Arnett, & McKenzie, ; Phinney, ) and access/use of global media and technology (Arnett, ) during these development periods.…”
mentioning
confidence: 99%